A brief overview of evolutionary developmental robotics. Issue 6 (14th October 2014) - Xu, Bo; Min, Huaqing; Xiao, Fangxiong
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This article aims to provide a brief overview of the field now known as "evolutionary developmental robotics (evo-devo-robo)", which is based on the concept and principles of evolutionary and development principles such as evolutionary developmental psychology, evolutionary developmental biology (evo-devo) and evolutionary cognitive neuroscience. Design/methodology/approach – Evo-devo-robo is a new field bringing together developmental robotics and evolutionary robotics to form a new research area. Basic concepts and the origins of the field are described, and then some basic principles of evo-devo-robo that have been developed so far are discussed. Findings – Finally, some misunderstand concepts and the most promising future research developments in this area are discussed. Originality/value – Basic concepts and the origins of the field are described, and then some basic principles of evo-devo-robo that have been developed so far are discussed. Finally, some misunderstood concepts and the most promising future research developments in this area are discussed.